Helicobacter pylori may be an initiating factor in newly diagnosed ulcerative colitis patients: A pilot study - Mansour, Loai (World J Clin Cases, 2018)
AIM: To directly visualize Helicobacter pylori (H. pylori) by the highly sensitive and specific technique of immunohistochemical staining in colonic tissue from patients newly diagnosed with ulcerative colitis (UC). METHODS: Colonoscopic biopsies from thirty patients with newly diagnosed UC and thirty controls were stained with Giemsa stain and immunohistochemical stain for detection of H. pylori in the colonic tissue. Results were confirmed by testing H. pylori Ag in the stool then infected patients were randomized to receive either anti H. pylori treatment or placebo. RESULTS: Twelve/30 (40%) of the UC patients were positive for H. pylori by Giemsa, and 17/30 (56.6%) by immunohistochemistry stain. Among the control group 4/30 (13.3%) and 6/30 (20 %) were positive for H. pylori by Giemsa and immunohistochemistry staining respectively. H. pylori was significantly higher in UC than in controls (P = 0.04 and 0.007). All Giemsa positive patients and controls were positive by immunohistochemical stain. Four cases of the control group positive for H. pylori also showed microscopic features consistent with early UC. CONCLUSION: H. pylori can be detected in colonic mucosa of patients with UC and patients with histological superficial ulcerations and mild infiltration consistent with early UC. There seems to be an association between UC and presence of H. pylori in the colonic tissue. Whether this is a causal relationship or not remains to be discovered.